Fatigue strengthening of damaged steel members using wire arc additive manufacturing - Ghafoori, Elyas S.; Dahaghin, Hamid; Diao, Chenglei; Pichler, Niels; Li, Lingzhen; Mohri, Maryam; Ding, Jialuo; Ganguly, Supriyo; Williams, Stewart (Elsevier, 2023)
In this study, a directed energy deposition (DED) process called wire arc additive manufacturing (WAAM) is employed for the fatigue strengthening of damaged steel members. Three steel specimens with central cracks were tested under a high-cycle fatigue loading (HCF) regime: (1) the reference specimen; (2) the WAAM-repaired specimen with an as-deposited profile, and (3) the WAAM-repaired specimen machined to reduce stress concentration factors (SCF). The corresponding finite element (FE) simulation of the WAAM process was calibrated using static experimental results, which revealed the main mechanism. The process was found to introduce compressive residual stresses at the crack tip owing to the thermal contraction of the repair. The FE results also revealed that stress concentration exists at the root of the as-deposited WAAM; this stress concentration can be mitigated by machining the WAAM to a pyramid-like shape. The fractography analysis indicated that the cracks were initiated at the WAAM-steel interface, and microscopic observations revealed that the microcracks were arrested by the porosities in the melted interface. The results of this pioneering study suggest that WAAM repair is a promising technique for combating fatigue damage in steel structures.
Keywords: Metal 3D-printing; Hybrid manufacturing; Fatigue repair; Fatigue life extension; Crack arrest